Pension Rules and Labour Market Mobility - Marloes Lammers; Hans H.G. Bloemen; Stefan S. Hochguertel (Tinbergen Institute, 2017)
This paper makes use of a natural experiment to examine effects of potential capital losses and general attractiveness of pension schemes on employees' propensity to change jobs. On January 1st 2004, the two largest pension funds in the Netherlands, for civil servants and for the health care sector, changed their pension scheme from a final salary to an average salary. This industry-leve change excludes the possibility that a negative correlation between having a job with an attractive pension scheme and the number of labour market transitions is driven by self-selection of workers into jobs with an attractive pension arrangement. Using individual data covering the entire Dutch population, we estimate discrete choice models for job-to-job transitions. The results show that the number of job transitions of civil servants significantly increased at the onset of the new pension rules. The changing pension rules affected the propensity to change jobs for individuals working in the health care sector only to a smaller extent.
Keywords: C35; J26; J32; J63; 330; Discrete Choice Models; Policy Evaluation; Labour market Flexibility; Pension Systems